Analysis of Patient Safety Culture using Hospital Survey on Patient Safety Culture (HSOPSC) in Seven Countries - Ilmidin Ilmidin; Nurul Syuhfal Ningsih (Lambung Mangkurat, 2022)
According to the World health Organization (WHO) there are more than 134 million side effects that occur in process treatment of health care, because of the unsafe treatments , there are 2,6 million people dead. This study aims to analyse the patient safety culture of seven countries as well as Ethiopia, United States, Philippines, Indonesia, Ghana, Iran, and Republic of China. This study uses the literature study method. The researcher focuses on positive responses based on the results of HSOPSC of those countries. The result of study found that there were 37,74% of the lowest responses in Staffing dimension and the highest responses were around 75.95% in teamwork within unit. The conclusion of the study found that the patient safety culture were around 53,18% of all dimensions, the lowest dimension was in staffing management, non-punitive response to errors, and frequency of events reported.